Blood pressure lowering effects of β‐blockers as add‐on or combination therapy: A meta‐analysis of randomized controlled trials. Issue 3 (8th February 2023) - Guo, Qian‐Hui; Zhu, Zhi‐Ming; Feng, Ying‐Qing; Lin, Jin‐Xiu; Wang, Ji‐Guang
Abstract: The authors performed a meta‐analysis to assess the efficacy of non‐atenolol β‐blockers as add‐on to monotherapy or as a component of combination antihypertensive therapy in patients with hypertension. The authors searched and identified relevant randomized controlled trials from PubMed until November 2021. Studies comparing blood pressure lowering effects of β‐blockers with diuretics, calcium channel blockers (CCBs), angiotensin‐converting enzyme inhibitors (ACEIs), or angiotensin receptor blockers (ARBs) were included. The analysis included 20 studies with 5544 participants. β‐blockers add‐on to monotherapy significantly reduced systolic and diastolic blood pressure as compared with non‐β‐blocker monotherapy (weighted mean difference in mm Hg [95% confidence interval]: −4.1 [−6.0, −2.2] and −3.7 [−4.6, −2.8], respectively). These results were consistent across the comparisons with diuretics (systolic pressure, −10.2 [−14.2, −6.2]; diastolic pressure, −5.4 [−8.2, −2.6]), CCBs (systolic pressure, −4.1 [−7.1, −1.0]; diastolic pressure, −2.8 [−4.1, −1.5]), and ACEIs/ARBs (systolic pressure, −2.9 [−4.3, −1.5]; diastolic pressure, −4.2 [−5.0, −3.4]). There was no significant difference in blood pressure lowering effects between combinations with and without a β‐blocker (systolic pressure, −1.3 mm Hg [−5.8, 3.2]; diastolic pressure, −.3 mm Hg [−2.7, 2.1]). Metoprolol add‐on or combination therapy had a significantly greater blood pressure reduction than non‐β‐blocker therapy (systolic pressure, −3.6 mm Hg [−5.9, −1.3]; diastolic pressure, −2.1 mm Hg [−3.5, −.7]). In conclusion, non‐atenolol β‐blockers are effective in lowering blood pressure as add‐on to monotherapy or as a component of combination antihypertensive therapy. In line with the current hypertension guideline recommendations, β‐blockers can and should be used in combination with other antihypertensive drugs.